Lecture 1: Linking the lab with the runner - McMillan, G.
There's often a "disconnect" between what the physiologists say and what those in the real world of training and racing say (and do!). In this lecture auhor presents a simple method to make the connection between science and reality and show you how to use this connection to improve your running. But one simply should use sports science to help one better understand how their training techniques can be applied to their individual fitness level and strengths and weaknesses.